The effectiveness of the dry laboratory strategy in acquiring biological concepts among the fifth scientific class students (Journal of the College of Basic Education, 2025)
The current research seeks to identify the effectiveness of the dry laboratory strategy in acquiring biological concepts among the fifth scientific class students. In order to achieve the objectives of the current research, the study relied on the quasi-experimental approach by designing a control group with a pre- and post-application, and in order to collect the necessary data and information, it was done Building a test to measure the biological concepts of biology, as well as making equivalencies between the experimental and control research groups. After applying the experiment, the study reached the following results:The dry laboratory strategy has a clear effectiveness in acquiring biological concepts for fifth scientific class students.2. There are statistically significant differences between both thee experimental and control groups, and these differences are in favor of the experimental group